2016
DOI: 10.1111/age.12445
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in coat colour (genotypes) supports major changes in the Nordic cattle population after Iron Age

Abstract: SummaryVariation in coat colour genotypes of archaeological cattle samples from Finland was studied by sequencing 69 base pairs of the extension locus (melanocortin 1-receptor, MC1R) targeting both a transition and a deletion defining the three main alleles, such as dominant black (E D ), wild type (E + ) and recessive red (e). The 69-bp MC1R sequence was successfully analysed from 23 ancient (1000-1800 AD) samples. All three main alleles and genotype combinations were detected with allele frequencies of 0.26,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…In addition, a comparative analysis by Niemi et al [36] of ancient DNA of cattle from Finland and contemporary Scandinavian cattle showed that the frequency of MC1R alleles exhibits changes over time that are similar to those found in studies of mitochondrial DNA and Y chromosome haplotypes.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In addition, a comparative analysis by Niemi et al [36] of ancient DNA of cattle from Finland and contemporary Scandinavian cattle showed that the frequency of MC1R alleles exhibits changes over time that are similar to those found in studies of mitochondrial DNA and Y chromosome haplotypes.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, a comparative analysis by Niemi et al [ 36 ] of ancient DNA of cattle from Finland and contemporary Scandinavian cattle showed that the frequency of MC1R alleles exhibits changes over time that are similar to those found in studies of mitochondrial DNA and Y chromosome haplotypes. At the locus of the MC1R gene as well as the other two markers there was a significant change in genotypes in Scandinavian cattle from the late Iron Age to the Middle Ages, followed by a period of slower change, continuing up to the present day.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Another gene found in a region of putative positive selection, the melanocortin 1 receptor (MC1R), was top-ranked in the hapFLK-reported region in GROUP1 and in the DCMS interval identified in the Altai Mountain breed. MC1R has a pleiotropic effect, known, among other traits, to influence coat colour in sheep [52] and cattle [53]. The microphthalmia transcription factor (MITF) is a regulator of melanocyte development, and is associated with coat colour in mouse Fig.…”
Section: Coat Colourmentioning
confidence: 99%
“…However, the molecular genetic mechanisms underlying coat colour regulation in minks are not fully understood because few candidate genes potentially involved in pigmentation have been identified except for the MLPH, LYST, tyrosinase (TYR), MITF and tyrosinase-related protein 1 (TYRP1) genes 4 8 . Despite considerable knowledge of the genetic regulation of coat colour in mice 9 – 11 , cows 12 , 13 , goats 14 , 15 , sheep 16 , 17 and pigs 18 20 , the molecular and cellular mechanisms regulating coat colour in fur-bearing species, such as mink, are not fully understood. This information is critical for enhancing our basic understanding of the regulation of melanogenesis and for identifying novel pharmacological and molecular genetics approaches to regulate or select for coat colour in fur-bearing species.…”
Section: Introductionmentioning
confidence: 99%